1998
DOI: 10.1002/(sici)1097-0185(199802)250:2<210::aid-ar11>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous looping, atrioventricular cushion dysplasia, and unilateral ventricular hypoplasia in the mouse embryos with right isomerism induced by retinoic acid

Abstract: An anomalous relation between the atrioventricular cushions and the interventricular septum appeared to have caused a restrictive inflow to the unilateral ventricle, leading to ventricular chamber hypoplasia on the ipsilateral side. Thus, we clarified that retinoic-acid treatment at the primitive streak stage disturbed cardiac looping and formation of atrioventricular cushion development, which secondarily influenced ventricular chamber development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…As the Tbx2 expression in the AVC region occurs earlier than that in the OFT region (Habets et al, 2002), the administration of RA at E8.5 might be too late to suppress Tbx2 expression in the AVC region. In fact, previous data indicated that abnormal AVC endocardial EMT was also induced by excess RA when embryos were treated with RA at E6.5 (Yasui et al, 1998). A second possibility is that different sensitivities to RA exist among different heart-forming lineages.…”
Section: Discussionmentioning
confidence: 96%
“…As the Tbx2 expression in the AVC region occurs earlier than that in the OFT region (Habets et al, 2002), the administration of RA at E8.5 might be too late to suppress Tbx2 expression in the AVC region. In fact, previous data indicated that abnormal AVC endocardial EMT was also induced by excess RA when embryos were treated with RA at E6.5 (Yasui et al, 1998). A second possibility is that different sensitivities to RA exist among different heart-forming lineages.…”
Section: Discussionmentioning
confidence: 96%
“…35,36 In this animal model, TGA could be found in the presence of both D-and L-loops of the ventricles (ie, complete TGA and congenitally corrected TGA), 35 and treatment with retinoic acid in mouse embryos also could induce looping anomalies with right isomerism. 37 Moreover, complete TGA (ie, with situs solitus and D-loop ventricle) can be present among heart defects of homozygous iv/iv mice presenting with a high prevalence of visceral heterotaxy and lateralization anomalies. 38 Animal models, therefore, support a common pathogenetic mechanism involved in causing some cases of complete TGA along with congenitally corrected TGA and other laterality defects.…”
Section: Discussionmentioning
confidence: 99%
“…34 Amino acid exchanges caused by missense mutations could alter the ability of PROSIT240 to interact with target activators or repressors. Understanding more about the mechanisms leading to dTGA might also help to determine whether dTGA could be considered a manifestation of a left-right laterality defect concerning the heart, a point that has been raised based on data from animal models 35,36 and the fact that ZIC3 and CFC1 mutations are detected both in patients with dTGA and in heterotaxy problems. 8,11 In animal models, most interestingly, Pitx2 Ϫ/Ϫ and Dvl Ϫ/Ϫ mice present with outflow tract abnormalities, including TGA and laterality defects.…”
Section: Muncke Et Al Prosit240 Mutations In Patients With Dtgamentioning
confidence: 99%